Structural Characterization, Antioxidant and Antibacterial Activities of a Novel Polysaccharide From Zingiber officinale and Its Application in Synthesis of Silver Nanoparticles - Jing, Yongshuai; Cheng, Wenjing; Ma, Yunfeng; Zhang, Yameng; Li, Mingsong; Zheng, Yuguang; Zhang, Danshen; Wu, Lanfang (Frontiers in Nutrition, 2022)
A novel polysaccharide (ZOP) was extracted from Zingiber officinale with ultrasonic assisted extraction method. The monosaccharide composition of ZOP was composed of GlcA, GalA, Glc, Gal and Ara, and the molar ratio was 1.97: 1.15: 94.33: 1.48: 1.07. Then, ZOP-NPs was prepared by nano-precipitation method, the particle size of ZOP-NPs was 230.5 nm and polydispersity index (PDI) was 0.260. ZOP-AgNPs and ZOP-NPs-AgNPs were prepared using ZOP and ZOP-NPs as reducing agent and characterized by ultraviolet-visible spectrophotometer (UV-Vis), fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), transmission electron microscope (TEM) and X-ray diffraction (XRD). The chelation rate of silver nanoparticles with polysaccharides was 68.70~82.12%. ZOP-AgNPs (0.5%, w/v; 1%, w/v) and ZOP-NPs-AgNPs (0.5%, w/v; 1%, w/v) exhibited a narrow particle size distribution of 31.1, 34.6, 25.1 and 27.6 nm, respectively. And the zeta potential values of them were-19.4, -21.6, -19.7 and -23.8 mV respectively. ZOP-NPs-AgNPs had better antioxidant and antibacterial activities than ZOP, ZOP-NPs and ZOP-AgNPs. In the present work, a simple and eco-friendly approach for the synthesis of silver nanoparticles (AgNPs) using ZOP and ZOP-NPs as reducing agent.